The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/pi.6284
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and dielectric properties of low‐density polyethylene/NaA zeolite composites

Abstract: The effect of the weight fraction of NaA zeolite on thermal properties (specific heat capacity, thermal diffusivity, thermal conductivity) and dielectric properties (electrical conductivity, real and imaginary electric permittivity) of composites based on low-density polyethylene (LDPE) and NaA zeolite is examined. Composite samples containing from 5 to 30 wt% zeolite are prepared using the compression molding technique. The degree of dispersion and the weight fraction of filler in the LDPE/NaA zeolite composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The dielectric constant, CTE, and density of LLEDP/COC are compared with previously reported thermoplastic composites, 48–58 and the results are presented in Table 4. It can be seen that LLDPE/COC exhibits a relatively good combination of properties compared with its counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constant, CTE, and density of LLEDP/COC are compared with previously reported thermoplastic composites, 48–58 and the results are presented in Table 4. It can be seen that LLDPE/COC exhibits a relatively good combination of properties compared with its counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, composites containing NaA zeolite additives at rates ranging from 5% to 30% by weight were prepared and it was observed that the thermal conductivity increased as the additive ratio increased. Similarly, a gradual increase in electrical conductivity was detected with increasing zeolite content 10 . Very recently, Al‐Jumaili et al studied the mechanical properties of LDPE/montmorillonite (MMT) films.…”
Section: Introductionmentioning
confidence: 96%